2012
DOI: 10.1111/j.1752-7325.2011.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Child and family health nurses' experiences of oral health of preschool children: a qualitative approach

Abstract: This study highlights that oral health problems are a significant segment of the child health problems identified by nurses in their daily work. The nurses perceived the problem of dental caries to be one of a lack of parental knowledge, and families should be educated not only on "what" but also on "how" to feed their children. The primary healthcare team should work collaboratively to educate families in a culturally appropriate way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
0
31
0
2
Order By: Relevance
“…Studies have demonstrated that parental perceptions are associated with clinical characteristics, as children with dental caries are more prone to having their oral health status rated as poor [15, 33, 34]. As parents/caregivers are responsible for their child’s health care and admit that oral health problems can be avoided, the perception of poor oral health may cause feelings of guilt [8, 17]. Moreover, the perception of poor oral health is associated with dental treatment needs in preschool children [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have demonstrated that parental perceptions are associated with clinical characteristics, as children with dental caries are more prone to having their oral health status rated as poor [15, 33, 34]. As parents/caregivers are responsible for their child’s health care and admit that oral health problems can be avoided, the perception of poor oral health may cause feelings of guilt [8, 17]. Moreover, the perception of poor oral health is associated with dental treatment needs in preschool children [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although dental health professionals explain the main methods for preventing dental caries [36], many parents fail to put these methods into daily practice [14, 18]. In such cases, parents/caregivers often feel accountable [8, 9] and worry about their child’s future opportunities in life [18]. Parental guilt with regard to cavitated lesions further demonstrates the negative impact of this oral health problem on quality of life [57, 35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral diseases can have resultant impact on communities' general health and well-being [13]. Dental caries being the most prevalent chronic childhood disease worldwide [14] whilst periodontal disease is a chronic infection of the gingiva and supporting tooth structures which is highly prevalent particularly among adults of low income communities [15]. Both periodontal disease and dental caries are typically asymptomatic conditions for long periods of time with only intermittent exacerbations [15].…”
Section: Introductionmentioning
confidence: 99%